Bioethical dilemmas on medical grounds – psychological perspective - Kaczmarczyk, Justyna A.; Szpringer, Monika (Medical Studies/Studia Medyczne, 2017)
The rapid development of medicine that has taken place in the last 10 years confronts personnel with new challenges that extend beyond life-saving treatments; they include moral, legal, and deontological dilemmas, which can be recognised as bioethical ones. The new discourse of patient’s participation in planning their treatment makes it impossible to remain indifferent to their expectations and will, the patient’s approval, and declaration of intent on the healing process, and at the same time not to respect their basic privileges guaranteed by law and those arising from the codes of ethics. Humans are a bio-psychophysical unity, and therefore should be perceived from a holistic perspective. This article presents the different dilemmas concerning the treatment of patients in the terminal stage of disease, including minors. It indicates the assessment and the prospect of death, from the child and adult perspective. It recognises patient’s rights, his/her autonomy, dignity, subjectivity, but also the responsibilities and duties of health care personnel, taking into account respect for the patient, his/her independence, the adequacy of activities, and reference to the principle of double effect.